Project Management Organisation in Public Authorities - A. I. Vasilyev; S. Ye. Prokofyev (Управленческие науки, 2016)
The aspects of implementing the system of project management into public authorities are considered in the article. The project management topicality is stipulated by new challenges in the system of Russia public administration. Executive bodies’ ability to implement the planned projects and tasks and reach the set goals in time and within the established budget is becoming crucially important under the modern conditions. The project management methods are intended to mobilize and structure the organization’s resources in reaching the projects targets. The project management on the basis of project approach possesses a number of merits which are mentioned in the article as well. The project management object is a project as a specially organized complex of works aimed at solving the definite task or reaching the definite goal which fulfillment is not limited in time but is also connected with consumption of concrete financial, material and labor resources. Consequently it is important to distinguish the project activity from the aggregate organization’s activity. For that purpose the article analyses the theoretical bases of project and process activity, defines their main peculiarities and differences. For the correct building of project management the organization systems principles are formulated and the most spreading spheres for management methods are mentioned. In conclusion the most important advantages of project approach implementation are stated.